2018
DOI: 10.31782/ijcrr.2018.10206
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Picrorhizakurroa Against Fumonisin B1 Induced Hepatotoxicity in Mice

Abstract: Objectives: The aim of the present study is to evaluate hepatoprotective effect of Picrorhizakurroaextracts (PKE) against Fumonisin b1 (Fb1) induced hepatotoxicity. Methods: Hepatoprotective analysis was done by estimating serum biochemical parameters Alanine aminotransferase (ALT) and aspartate aminotransferase (AST), antioxidant enzyme status lipid peroxidations, ROS generation, and protein carbonyls were also estimated to know the oxidative damage. Further protein expressions were confirmed by western blott… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…Our findings confirm reports of increased liver enzyme levels by the same FB 1 dose (2.25 mg/kg bw) ( 24 26 ). Administration of resveratrol in our study attenuated these effects to the levels no longer significantly higher than control.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings confirm reports of increased liver enzyme levels by the same FB 1 dose (2.25 mg/kg bw) ( 24 26 ). Administration of resveratrol in our study attenuated these effects to the levels no longer significantly higher than control.…”
Section: Discussionsupporting
confidence: 92%
“…The authors showed that ROS production was related to mitochondrial complex I, CYP450 and the NADPH oxidase system. KRUPASHREE et al (2018) reported that SOD, CAT, GSH-Px, and GSH levels decreased and MDA levels increased in hepatotoxicity induced by FB1 (2.25 mg) in BALB/c mice.…”
Section: Discussionmentioning
confidence: 96%
“…In this study, the effect of resveratrol on SIRT2, SIRT3 protein expressions, 8-OHdG, reduced GSH, nitric oxide and MDA levels were investigated in fumonisininduced hepatotoxicity in BALB/c mice. It has been reported that exposure to FB1 disrupts the redox-system and exerts this effect by increasing reactive oxygen species (ROS), lipid peroxidation, oxidative DNA damage and reducing antioxidant GSH content, GSH-Px and SOD levels (ABEL and GELDERBLOM, 1998;EL-NEKEETY et al, 2007;KRUPASHREE et al, 2018;MARY et al, 2012). The antioxidant approaches in in vivo and in vitro studies generally aim to reduce the toxic effects of FB1.…”
Section: Discussionmentioning
confidence: 99%
“…picrosides I and II, Kutkins, kutkosides, cucurbitacin, sterols/triterpenes and simple phenols such as apocynin, vanillic acid most explored phytoactives from ethanolic and methanolic extracts [ 7 , 8 ]. The dried roots and rhizomes of the plant are commercially important parts, and they are used to treat a variety of ailments, including spleen disorders, liver diseases, and allergy issues [ 9 , 10 ]. The use of traditional medicinal plants in the form of functional foods and nutraceuticals has acquired significance in the modulation of numerous diseases, P. kurroa is one such therapeutic herb through which we could avoid the intake of chemical drugs to treat these disorders without any side effects.…”
Section: Introductionmentioning
confidence: 99%